2022
DOI: 10.1002/14651858.cd007411.pub5
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants for male subfertility

Abstract: Trusted evidence. Informed decisions. Better health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
9

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 241 publications
1
47
0
9
Order By: Relevance
“…Thirteen studies (1813 men) had data on DNA fragmentation; however, due to high heterogeneity, pooling of these results was not possible. Regarding reproductive outcomes, like the previous 2019 Cochrane review, the authors found that antioxidants may lead to increased live birth rates (OR 1.43, 95% CI 1.07 to 1.91, p = 0.02, I 2 = 44%) [ 73 ]. Again, however, only a limited number of studies included live birth rate as an endpoint (246 live births from 1283 couples in 12 small- or medium-sized studies), leading the authors to consider this increase in live birth rate “very low-certainty evidence”.…”
Section: Methods For Overcoming High Sdfmentioning
confidence: 65%
See 1 more Smart Citation
“…Thirteen studies (1813 men) had data on DNA fragmentation; however, due to high heterogeneity, pooling of these results was not possible. Regarding reproductive outcomes, like the previous 2019 Cochrane review, the authors found that antioxidants may lead to increased live birth rates (OR 1.43, 95% CI 1.07 to 1.91, p = 0.02, I 2 = 44%) [ 73 ]. Again, however, only a limited number of studies included live birth rate as an endpoint (246 live births from 1283 couples in 12 small- or medium-sized studies), leading the authors to consider this increase in live birth rate “very low-certainty evidence”.…”
Section: Methods For Overcoming High Sdfmentioning
confidence: 65%
“…Both MOXI and FAZST were included in the most recent version of the Cochrane review, published in 2022 [ 73 ]. Of the 90 studies and over 10,000 subfertile men included in the updated systematic review, 65 studies were included in the meta-analysis.…”
Section: Methods For Overcoming High Sdfmentioning
confidence: 99%
“…Overall, there is no evidence that antioxidant therapy increases the chance of miscarriage. Therefore, subfertile couples should be advised that the existing research on the efficacy of antioxidant therapy in improving male fertility is inconclusive [ 103 ]. The question of antioxidant therapy that could mitigate the toxicity of EDCs in men facing fertility problems is therefore still open, and needs to be further researched.…”
Section: Resultsmentioning
confidence: 99%
“…While a healthy diet is certainly conducive to a healthy body and hence a potential association with gamete quality [ 120 ] and genome stability, we are a long way from concluding that the supplementation of the diet would be beneficial for male infertility. Large, randomized placebo-controlled trials are required to address this question as concluded in the last Cochrane review of antioxidants for male infertility [ 121 ].…”
Section: Discussionmentioning
confidence: 99%